POTENSI PERTANIAN BERBASIS DUKUNGAN KOMUNITAS SEBAGAI SOLUSI PERSOALAN PETANI KECIL DI INDONESIA - Sulistyowati, Catharina Any; Afiff, Suraya A; Baiquni, M; Siscawati, Mia (Analisis Kebijakan Pertanian, 2024)
The agricultural sector plays a strategic role in the Indonesian economy. Unfortunately, many farmers still face problems such as low income, low productivity, crop failure, price fluctuations, infertile land, and debt bondage. Despite its many efforts, the Indonesian government has not successfully solved these problems effectively. So far, none of those efforts focused on raising consumer awareness to support small farmers. Community-supported agriculture (CSA) is an initiative toward a more sustainable food system. CSA members support small farmers implementing sustainable agriculture to produce healthy food. This article describes the key elements of CSA development and explores CSA potencies to solve the problems of small farmers in Indonesia. Articles on CSA from Scopus-indexed social science journals from 1994-2022 and related literature were used as data sources for this literature study. This study found that the key elements to implement sustainable agriculture through CSA at the local level are (1) financing the transition process from chemical to sustainable agriculture, (2) access to land, (3) farmers' quality of life, and (3) farmers' capacity.  Key elements for gaining consumer support for CSA are (1) consumer motivation and awareness, (2) member contributions, (3) member inclusiveness, and (4) member sustainability. It is also crucial to support institutional development and develop supporting policies.